Aastaks 2025 Eestile üks põhja- ja lõunalinnakuga ülikoolihaigla - Starkopf, Joel; Talving, Peep; Siigur, Urmas; Peedu, Agris; Luts, Katrin; Asser, Toomas (Eesti Arst, 2018)
Eesti Arst 2018; 97(4):179–180